Equilíbrio corporal e função vestibular em pacientes com esclerose múltipla - Cusin, Flavia Salvaterra [UNIFESP] (2019)
Objective: assess body balance and vestibular function in patients with relapsing-remitting multiple sclerosis (RRMS). Method: We included 79 individuals aged between 18 and 65 years, males and females, distributed in two groups: experimental (n=51) and control (n=28). The experimental group was composed of patients with RRMS, and the control was homogeneous in age, gender and body mass index by healthy individuals, in relation to the experimental group. The neurotological assessment consisted of anamnesis, Dizziness Handicap Inventory (DHI), Visual Vertigo Analogue Scale (VVAS), vestibular function assessment with Videonystagmography (VNG), Video Head Impulse Test (vHIT) and Static posturography (Tetrax IBSTM). Results: upon performing Tetrax IBSTM, patients with RRMS showed higher or lower values of general stability, weight distribution, postural oscillation synchronization, risk of falling indices, and of the frequency ranges of postural oscillation in two, five or all eight sensory conditions, in relation to controls. Vestibular, visual and/or somatosensory dysfunction of peripheral type (51 %) prevailed over the central type. The group with RRMS, with an expanded disability status scale higher than three points, showed a higher risk of falling compared with the one with scores lower than or equal to three points (p=0,003). There was a positive correlation of the fall risk index with total DHI score (s=0,380; p=0,006) and with VVAS (s=0,348; p=0,012). In VNG, the group with RRMS showed increased right (p=0,035) and left (p=0.030) latency and decreased right velocity (p=0,007) of saccadic movements; decreased right (p=0,002) and left (p<0.001) gain of pendular eye tracking; higher values (p=0,002) of the post-caloric nystagmus velocity, in relation to the control group; and presence of semi-spontaneous nystagmus; peripheral or central ,5%), unilateral peripheral deficit (17, and central (15,7%) vestibular dysfunction were identified in the group with RRMS. In vHIT, the group with RRMS showed decreased gain of the vestibulo-ocular reflex (VOR) in four semicircular canals (CSCs), left lateral (p=0,017), right anterior (p=0,004), left posterior (p<0,001) and right posterior (p=0,042), in relation to control; decreased VOR happened in nine (17,6%) cases of RRMS. Conclusion: patients with RRMS may have an inability to maintain body balance, with risk of falling and/or peripheral or central vestibular dysfunction.